Case-based insights into rework costs of residential building projects in China. Issue 4 (3rd July 2020) - Liu, Qinjun; Ye, Gui; Feng, Yingbin; Wang, Chaoyun; Peng, Yi
Abstract: Rework has been identified as a major cause of cost overran of residential building projects. This study aims to investigate the magnitude of rework costs generated by different sources for residential building projects in China. Six residential building projects were selected as sample cases; rework activities and their detailed cost information were collected and analysed. The result revealed that average rework cost of residential building projects was 4.95% of the total project cost. The majority of rework costs were generated by three sources including contractor field management (20.10%), design management (18.91%) and client management (14.73%). It was also found that the main liability bearers of rework costs did not take corresponding responsibilities. The establishment of rework costs allocation mechanism is therefore required to enhance the sense of responsibility among different entities. The magnitude of rework cost may well motivate them take collaborative actions to reduce rework cost. This article provides valuable empirical data for practitioners to understand the major sources of rework costs and main liability-bearers. Therefore, practitioners can take targeted measures to address certain key factors that cause rework based on the data. Above all, this study will bring benefit to the construction industry as well as the whole society.